Trait Mindfulness Is Associated With the Self-Similarity of Heart Rate Variability - Sun, Shasha; Hu, Chuanlin; Pan, Junhao; Liu, Chengyi; Huang, Miner (Frontiers in Psychology, 2019)
Previous studies have linked trait mindfulness with better self-regulation and adaptation. Heart rate variability (HRV) is a good physiological indicator of the capacity for self-regulation and adaptation. The present study explored the relationship between trait mindfulness and HRV from the viewpoint of crosstalking between different HRV parameter pairs. We measured the trait mindfulness of seventy-four undergraduate students and recorded nine HRV parameters during the following four consecutive experimental phases: 1) calming phase, 2) mental arithmetic task phase, 3) recovery phase, and 4) mindfulness practice phase. The relationship between trait mindfulness and HRV was explored at the following three levels: 1) absolute level, i.e., HRV parameters in four different states, 2) difference-change level, i.e., differences in HRV parameters between different states, and 3) the crosstalking level, i.e., self-similarity of crosstalking HRV parameter pairs. The results supported the following hypothesis: trait mindfulness, as measured by the Mindful Attention Awareness Scale (MAAS), was significantly and positively correlated with the self-similarity of crosstalking HRV parameter pairs but not significantly correlated with the HRV parameters at the difference-change and absolute levels. These findings indicate that as trait mindfulness increases, the ability to maintain autonomic nervous system (ANS) function homeostasis improves.